Production of potable water from Gomti River by using modified double slope solar still with external mounted reflectors. (October 2020) - Patel, Suresh Kumar; Kumar, Brajesh; Pal, Piyush; Dev, Rahul; Singh, Dhananjay
Highlights: The performance of modified still with external mounted reflectors was investigated. Physicochemical parameters and WQI of Gomti river water were analyzed. Thermal efficiency of this model was obatained 10.4% and 10.0% in summer and winter seasons respectively. Cost analysis has been carried out. Abstract: The aim of this study is to improve the production of potable water through ultra modified double slope solar still (UMDSSS) by harvesting of direct solar energy as well as diffused radiation through transparent side walls. The setup was fabricated in combination with FRP and transparent acrylic sheets with a total basin area of 2 m 2 . Reflectors angles (30°, 45°, 60°, and 75°) were optimized for climatic conditions of Lucknow (26°30′ N, 80°13′ E), U.P., India. On the basis of productivity, optimized reflector angle has been found as 60°. The experimental and theoretical studies were carried out in the different seasons of year 2018. The basin water depth and glass cover tilt angle have been taken as 1.0 cm and 15° respectively. Our experimental investigation shows that the cumulative distillate productivity was obtained as 9157 ml/day and 6630 ml/day during summer and winter season, respectively at 60° reflector angle. The performance evaluation has been carried out in terms of physicochemical environmental parameters, productivity, and economic analysis. On the basis of economic analysis, the payback period was found 111 days and thermal efficiency of ultramodified solar still is higher 10.4% in summer and 10.0% in winter than that modified solar still.